2020
DOI: 10.1021/acs.langmuir.0c02807
|View full text |Cite
|
Sign up to set email alerts
|

Surface Freezing of Cetyltrimethylammonium Chloride–Hexadecanol Mixed Adsorbed Film at Dodecane–Water Interface

Abstract: The surface freezing transition of a mixed adsorbed film containing cetyltrimethylammonium chloride (CTAC) and n-hexadecanol (C16OH) was utilized at the dodecane–water interface to control the stability of oil-in-water (O/W) emulsions. The corresponding surface frozen and surface liquid mixed adsorbed films were characterized using interfacial tensiometry and X-ray reflectometry. The emulsion samples prepared in the temperature range of the surface frozen and surface liquid phases showed a clear difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…We demonstrate here that such temperature-controlled curvature inversion is possible in a capillary-contained macroscopic water–oil interface. The inversion occurs under the joint, interrelated, action of two nanoscale effects: one is the interfacial freezing (IF), whereby a crystalline monolayer spontaneously forms at the interface at a temperature T s . The freezing switches the temperature-slope of the interfacial tension, γ ow , from slightly negative at T > T s to strongly positive at T < T s , causing γ ow to decrease upon cooling and vanish at some T SE , above the bulk freezing point of the oil (cf. Supporting Information (SI) Figure S1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrate here that such temperature-controlled curvature inversion is possible in a capillary-contained macroscopic water–oil interface. The inversion occurs under the joint, interrelated, action of two nanoscale effects: one is the interfacial freezing (IF), whereby a crystalline monolayer spontaneously forms at the interface at a temperature T s . The freezing switches the temperature-slope of the interfacial tension, γ ow , from slightly negative at T > T s to strongly positive at T < T s , causing γ ow to decrease upon cooling and vanish at some T SE , above the bulk freezing point of the oil (cf. Supporting Information (SI) Figure S1).…”
mentioning
confidence: 99%
“…Indeed, T u is systematically lower than T s by a few °C. Since the interfacially frozen γ ow decreases dramatically ,,,, upon cooling below T s (see SI Figure S1), γ ow ( T u ) ≪ γ ow ( T s ). For the presently studied C 16 :C 18 TAB:C 16 OH combinations, γ ow tends to zero at T SE , a few °C below T s .…”
mentioning
confidence: 99%
“…This structure also explains the T d reduction in the C 17 OH‐doped system: the different OH orientation in odd alcohols [ 33 ] renders the bilayer‐stabilizing hydrogen bonds less favorable, yielding a reduction of the corresponding T s and T d . The high entropy loss upon the interfacial freezing, reported for the alcohol‐doped systems, [ 28,30 ] is similarly rationalized by the formation of a bilayer. As the number of conformational degrees of freedom per unit area is (roughly) twice larger for a molecular bilayer compared to a monolayer, [ 31 ] the larger entropy loss reported in the literature [ 28,30 ] strongly supports our conclusions.…”
Section: Resultsmentioning
confidence: 79%
“…Our recent studies [ 28,29 ] revealed a dramatic increase in T s and T d upon doping of C 18 TAB‐stabilized C 16 alkane droplets by sub‐percent concentrations of hexadecanol [CH 3 (CH 2 ) m − 1 OH, denoted: C m OH, with m = 16]. This increase, along with the unusually large interfacial entropy loss measured [ 28,30 ] at T s , suggests that the structure of the interfacial crystal is radically altered by the incorporation of the long‐chain alcohol molecules. Yet, no structural studies of alcohol‐doped emulsion interfaces have been hitherto reported, let alone systematic investigations of alcohol doping effects on self‐faceting.…”
Section: Introductionmentioning
confidence: 92%
“…Mixed adsorbed film of a surfactant and n -alkane shows a first-order transition from a two-dimensional liquid to solid states at the air–water and the oil–water interfaces upon cooling. These surface freezing transitions were driven by the enhanced lateral van der Waals interaction between surfactant chains and incorporated n -alkanes and lead to a stable oil-in-water emulsions. , Furthermore, it was also reported that the surface-frozen layer at the oil–water interface induced the self-shaping or faceting of oil droplets placed in surfactant solution. Mixing of n -alkanes in surfactant-adsorbed films therefore attracts widespread attention in emulsion science and morphology control of related surfactant systems.…”
Section: Introductionmentioning
confidence: 99%